Identification and characterization of a novel gene involved in glandular trichome development in Nepeta tenuifolia - Zhou, Peina; Dang, Jingjie; Shi, Zunrui; Shao, Yongfang; Sang, Mengru; Dai, Shilin; Yue, Wei; Liu, Chanchan; Wu, Qinan (Frontiers in Plant Science, 2022)
Nepeta tenuifolia is a medicinal plant rich in terpenoids and flavonoids with antiviral, immunoregulatory, and anti-inflammatory activities. The peltate glandular trichome (PGT) is a multicellular structure considered to be the primary storage organ for monoterpenes; it may serve as an ideal model for studying cell differentiation and the development of glandular trichomes (GTs). The genes that regulate the development of GTs have not yet been well studied. In this study, we identified NtMIXTA1, a GT development-associated gene from the R2R3 MYB SBG9 family. NtMIXTA1 overexpression in tobacco resulted in the production of longer and denser GTs. Virus-induced gene silencing of NtMIXTA1 resulted in lower PGT density, a significant reduction in monoterpene concentration, and the decreased expression of genes related to monoterpene biosynthesis. Comparative transcriptome and widely targeted metabolic analyses revealed that silencing NtMIXTA1 significantly influenced the expression of genes, and the production of metabolites involved in the biosynthesis of terpenoids, flavonoids, and lipids. This study provides a solid foundation describing a mechanism underlying the regulation of GT development. In addition, this study further deepens our understanding of the regulatory networks involved in GT development and GT development-associated metabolite flux, as well as provides valuable reference data for studying plants with a high medicinal value without genetic transformation.